PS02.247: TWO CASES OF NEUROENDOCRINE CARCINOMA OF ESOPHAGOGASTRIC JUNCTION. (5th March 2019) - Yamada, L E O; Ohki, Shinji; Ujiie, Daisuke; Tada, Takeshi; Hanayama, Hiroyuki; Saze, Zenichiro; Momma, Tomoyuki; Hayase, Suguru; Gonda, Kenji; Nirei, Azuma; Okayama, Hirokazu; Sakamoto, Wataru; et al.
Abstract: Background: Neuroendocrine cell carcinoma (NEC) of the esophagogastric junction is rare and usually has a very poor prognosis. Methods: Here we present two cases of NEC occurred in the esophagogastric junction. Results: Case 1 A 50-year-old man was admitted to the introduction origin medical institute with an abdominal pain and dysphagia. Upper gastrointestinal endoscopy revealed a type 2 tumor at the esophagogastric junction, and the pathological examination showed the diffuse proliferation of relatively homogeneous tumor cell with chromatin-enriched nuclear and immunohistologically, the tumor cells were positive for Chromogranin A, CD56, AE1/3. MIB-1 index was 80%, we diagnosed neuroendocrine carcinoma (small cell type). TNM Stage was GE, Type 3, cT4, cN1, cM0 cStage IIIB (ENETS TNM classification) He had undergone total gastrectomy and lower esophagectomy with transhiatal approach and 2 field of lymph node dissection. Pathological examination revealed NEC component developed under the muscularis mucosa, differentiated adenocarcinoma localized upper the muscularis mucosa and Chromogranin A positive cells were scattered inside. Pathological findings showed NEC (MIB-1 72.5%) with tub1, 70 × 56 mm, pT3 pN1(7/36), stage IIIB (HER2 score0). Adjuvant chemotherapy using S-1 was started, but the follow up CT showed recurrence in mediastinum, left subclavian and paraaortic lymph nodes 7 months after surgery. S-1 followed by CPT-11 + CDDP, CT showed the shrinkage of paraaortic lymph nodes metastasis. The patient alive for 55 months without any evidence ofprogression being continued chemotherapy. Case 2 A 57-year-old man was admitted to the introduction origin medical institute with dysphagia. Upper gastrointestinal endoscopy revealed a type 2 tumor at the esophagogastric junction, and the pathological examination showed NEC (small cell type). CT and PET revealed mediastinal lymph node metastasis, aortic invasion and adrenal metastasis. TNM stage was NEC, EG, cT3, cN1, cM1 cStage IV. We performed a systemic chemotherapy with CPT-11 + CDDP, the evaluation of treatment effect after 5 course chemotherapy revealed partial response. However the patient underwent the endoscopic stent graft due to stenosis, and died due to progressive disease 18months after chemotherapy induction. Conclusion: We reported here two cases of NEC occurring in the esophagogastric junction. It's clinical behavior remains unclear and the treatment strategy for NEC of esophagogastric junction is not established. Further investigation of accumulated cases of this rare entity is necessary. Disclosure: All authors have declared no conflicts of interest.